2006
DOI: 10.1007/s10815-005-9008-y
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized trial of conventional in vitro fertilization versus intracytoplasmic sperm injection in unexplained infertility

Abstract: There were no differences in clinical outcomes associated with IVF versus ICSI in the treatment of unexplained infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 16 publications
2
52
1
Order By: Relevance
“…We observed a lower rate of fertilization failure with conventional IVF than reported in split IVF-ICSI studies, which may also account for the finding that our fertilization rates were not different. Similar to other reports, we found no difference in the transfer rate or cryopreservation rate of embryos fertilized by ICSI or conventional IVF suggesting that insemination method does not alter embryo development (7, 10,23). Data regarding the effect of insemination method on implantation rate, clinical PR, or live birth rate are not reported in the literature given that studies of split IVF-ICSI have included mixed transfers of embryos fertilized by IVF or ICSI.…”
Section: Discussionsupporting
confidence: 90%
“…We observed a lower rate of fertilization failure with conventional IVF than reported in split IVF-ICSI studies, which may also account for the finding that our fertilization rates were not different. Similar to other reports, we found no difference in the transfer rate or cryopreservation rate of embryos fertilized by ICSI or conventional IVF suggesting that insemination method does not alter embryo development (7, 10,23). Data regarding the effect of insemination method on implantation rate, clinical PR, or live birth rate are not reported in the literature given that studies of split IVF-ICSI have included mixed transfers of embryos fertilized by IVF or ICSI.…”
Section: Discussionsupporting
confidence: 90%
“…Though it has been suggested that 6-10 oocytes is the ideal quantity to optimize the number of embryos ultimately transferred [21], retrospective analyses of poor response cycles and subsequent fertilization and pregnancy rates suggest that embryo transfer is still possible in this patient population and cycles should not be cancelled [19,22,23]. While there have been prospective trials to compare IVF outcomes in CI versus ICSI, women with poor ovarian response [24] or previous low responders [25] have had cycles cancelled or have been excluded. In couples without poor response to COH, ICSI has no proven benefit over CI and is a more invasive and expensive technique [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…While there have been prospective trials to compare IVF outcomes in CI versus ICSI, women with poor ovarian response [24] or previous low responders [25] have had cycles cancelled or have been excluded. In couples without poor response to COH, ICSI has no proven benefit over CI and is a more invasive and expensive technique [24][25][26][27][28]. Prospective randomized trials studying low response to COH have not been performed.…”
Section: Discussionmentioning
confidence: 99%
“…While this approach has been tweaked and refined over the last 3-4 decades, the principles have remained. Contemporary human IVF/CI fertilization rates vary greatly, from 50 to 70% (Bhattacharya et al, 2001;Foong et al, 2006) and a 'true fertilization rate' following IVF/CI is unknown due to the presence of cumulus cells and inability to fully determine maturity of the oocyte within the cumulus mass. Since immature oocytes can be penetrated by sperm at the time of insemination, lack ability to form pronuclei or developmentally competent embryos, and yet still can progress to metaphase II (Van Blerkom et al, 1994), this interferes with a calculation of 'true fertilization'.…”
Section: Conventional Inseminationmentioning
confidence: 99%